SPECIFIC AND PERSPECTIVES UKRAINIAN POLITICAL REGIME - Гайко, О.С. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science")
Specificity of the Ukrainian political regime through the lens of the privatization of public institutions and political players and its prospects under the existing internal and external threats are discussed. Catch-up model of development of Ukrainian political institutions is criticized.